Evaluación de la transmisión de video en redes móviles ad-hoc mediante el simulador de redes ns-3. - Macas Torres, Fernanda Judith (2019)
This research describes the study carried out to implement a methodology in order to evaluate the transmission quality of coded video streams according with the standard MPEG-4 and H264 and the simulations carried out to sustain this methodology. Initially the research is based in a problematic situation for which objectives are set that help to find the effective solution, for what is necessary to do a literature review to get into the issues concerning in this work principally in the Ad Hoc networks analysis, and then get into to the study of the standards MPEG-4 and H264 and finally in the parameters which are taken into account for the evaluation of the video transmission. Into the proposed methodology is the process to follow for obtain the results through the comparative of the video service quality metrics in the standards MPEG-4 and H264, integrating multiple software tools that will be used in the different stages as they are: coding, encapsulation of video, network simulation and results analysis. With the final purpose to evaluate the video transmission are proposed three different cases of simulations are proposed whose node densities are different for each one of them. In these simulations was evaluated quality of service parameters as end to end delay, jitter, I, P, B frame loss, total frame loss, transmission and reception rate and the video quality in PSNR and MOS terms Keywords: MPEG-4, H264, PSNR, MOS, AODV, FFMPEG, Evalvid, video, NS-3, frames, standard, codec, ad-hoc, mobile networks.